Prospek dan Tantangan Pengembangan Koperasi di Indonesia Pasca Undang-Undang Nomor 17 Tahun 2012 tentang Perkoperasian - Raharja, Sam’un Jaja (Jurnal Administrasi Bisnis, 2013)
Revision of Law No. 25 of 1992 to Act No. 17 of 2012 on Cooperatives has afundamental and significant change. The definition of a cooperative as a cooper-ative business entity into cooperative as a legal entity, carries implications for theprocedures, requirements and ratification institutional establishment of cooperatives,and similar institutional treatment with other business areas such as private andstate-owned enterprises .The implications of these changes bring prospects for the co-operative devel-opment, because cooperatives establishment based on the real needs of cooperativeeconomic venture capital in accordance with the purpose of its founding. While thechallenges faced in implementation of laws is the severity of the terms and conditions,procedures for the establishment and ratification of cooperative legal entity. It will bean obstacle for cooperative was establish and people who want to set up, but notproper economicallyThis article is intended to (1) discuss how the prospects and challenges of coop-erative development and (2) formulate policy suggestions cooperative developmentof post- law No. 17 of 2012.Keywords: cooperative, institutional business, policy development